Interarchive : archivarische Praktiken und Handlungsräume im zeitgenössischen Kunstfeld = Archival practices and sites in the contemporary art field - von Bismarck, Beatrice; Feldmann, Hans-Peter, 1941-; Eichele, Sonja; Universität Lüneburg. Kunstraum (Köln : König, 2002)
"This book documents and extends the exhibition-project 'Interarchiv' of the Kunstraum der Universität Lüneburg in co-operation with Hans-Peter Feldmann and Hans Ulrich Obrist, 1997-2002"--Colophon.
German, English and French.
Includes bibliographical references.
boek
Keywords: Art archives -- Methodology; Art archives -- Exhibitions; Art archives -- Computer network resources -- Exhibitions